Effectiveness of permethrin standard and modified methods in scabies treatment (Medical Journal of Indonesia, 2014)
Background: Permethrin is the drug of choice for scabies with side effects such as erythema, pain, itching and prickling sensation. Whole-body (standard) topical application of permethrin causes discomfort; thus, modified application of permethrin to the lesion only, followed with baths twice daily using soap was proposed. The objective of the study is to know the effectiveness of standard against lesion-only application of permethrin in scabies treatment. Methods: An experimental study was conducted in pesantren in East Jakarta and data was collected in May-July 2012. Diagnosis of scabies was made through anamnesis and skin examination. Subjects positive for scabies were divided into three groups: one standard method group (whole-body topical application) and two modified groups (lesion-only application followed by the use of regular soap and antiseptic soap group). The three groups were evaluated weekly for three consecutive weeks. Data was processed using SPSS 20 and analyzed by Kruskal-Wallis test. Results: Total of 94 subjects was scabies positive (prevalence 50%) but only 69 subjects were randomly picked to be analyzed. The cure rate at the end of week III of the standard method group was 95.7%, modified treatment followed by the use of regular soap was 91.3%, and modified treatment followed by the use of antiseptic soap was 78.3% (p = 0.163). The recurrence rate of standard treatment was 8.7%, modified treatment followed by the use of regular soap was 13% and modified treatment followed by the use of antiseptic soap was 26.1% (p = 0.250). Conclusion: The standard scabies treatment was as effective as the modified scabies treatment.